2015
DOI: 10.1021/tx500323h
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Insecticides Induce NADPH Oxidase-Dependent Reactive Oxygen Species in Human Monocytic Cells via Phospholipase A2/Arachidonic Acid

Abstract: Bioaccumulative organohalogen chemicals, such as organochlorine (OC) insecticides, have been increasingly associated with disease etiology; however, the mechanistic link between chemical exposure and diseases, such as atherosclerosis, cancer, and diabetes, is complex and poorly defined. Systemic oxidative stress stemming from OC exposure might play a vital role in the development of these pathologies. Monocytes are important surveillance cells of the innate immune system that respond to extracellular signals p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…Consequently, these chemicals tend to bioaccumulate in fatty tissues and release slowly with time, causing oxidative stress. Recent reports suggest that these chemicals activate Nox complex through activation of phospholipases A 2 /arachidonic acid (PLA 2 /AA) in monocyte/macrophages (Mangum et al 2015). Monocytes treated with organochlorinated compounds enhanced Nox assembly and activation (Mangum et al 2015).…”
Section: Organochlorine Pesticides and Nadph Oxidase Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, these chemicals tend to bioaccumulate in fatty tissues and release slowly with time, causing oxidative stress. Recent reports suggest that these chemicals activate Nox complex through activation of phospholipases A 2 /arachidonic acid (PLA 2 /AA) in monocyte/macrophages (Mangum et al 2015). Monocytes treated with organochlorinated compounds enhanced Nox assembly and activation (Mangum et al 2015).…”
Section: Organochlorine Pesticides and Nadph Oxidase Activationmentioning
confidence: 99%
“…Recent studies have shown that organochlorine insecticides ( trans -nonachlor, dieldrin, and DDE) induced enhanced expression of phospho-p47 phox and enhanced its membrane localization (Mangum et al 2015). Mechanistically, this was attributed to (PLA 2 ) activation, leading to increased arachidonic acid and eicosanoid production in monocytes treated with organochlorinated compounds (Mangum et al 2015).…”
Section: Organochlorine Pesticides and Nadph Oxidase Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PV interneurons are susceptible to oxidative stress in response to adverse stimulation [15] and nicotinamide adenosine dinucleotide phosphate (NADPH) oxidases 2 (NOX2) mediates excessive reactive oxygen species (ROS) production [16,17], we further hypothesized that NOX2-induced excessive oxidative stress can lead to phenotype loss of PV interneurons and consequent behavioral impairments in rats with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Another OCP, trans-nonachlor, has been demonstrated to promote the production of intracellular reactive oxygen species by increasing the activity of NADPH oxidase in human monocytes. Interestingly, DDE did not cause a similar effect [Mangum et al 2015], indicating that these compounds could have different target cells and/or modes of action.…”
Section: Effects Of Popsmentioning
confidence: 95%